Self-assessment of health and physical fitness by young adults practising sport - Małgorzata Kałwa; Halina Guła-Kubiszewska; Urszula Dębska; Wojciech Starościak (Kazimierz Wielki University, 2016)
Introduction: Practising sport and engaging in physical activity at a young age is meant to increase the level of a person's physical fitness and health. Yet, the generation of 20-year-olds - former and active sportspersons - assess their general physical fitness and health as worse than good. Therefore, does practising sport, in the self-assessment of young persons, really improve one's health and physical fitness? Purpose: The purpose of this research was to diagnose the subjective assessment of fitness and a sense of health among young adults practising sport as well as former sportspersons in comparison with the self-assessment of non-training persons. Materials and methodology: 1153 adult persons aged 19-28 were surveyed. Those persons were supposed to perform a self-assessment of their health and physical fitness and report the pain disorders that they experienced. The group surveyed included 484 ex-sportspersons, 450 active sportspersons and 212 persons who had never practised sport. The survey used a 1-5 assessment scale. Results: The survey participants assessed their general physical fitness level at 3.82 ±1.00 and their health level at 3.88 ±1.10. In comparison with the other groups the sportspersons gave their fitness a better mark despite the largest number of pain disorders experienced. The result of health self-assessment did not differ among the groups. Sportspersons and ex-sportspersons indicated injuries and the pain felt, especially in the cervical and thoracic spine, the hips and the head, and complained more frequently about shortness of breath. Conclusions: Practising sport at a young age does not significantly alter the self-assessment of health among young persons. An average sportsperson experiences at least one pain disorder that correlates with a lower sense of good health. The highest frequency of associated pain disorders is observed in sportspersons, with the pain being located mainly in the area of the cervical and thoracic spine and the hips. The frequency of pain in the lower limbs is inversely proportional to one's overall training period.